Arguments against the Christian religion in Amsterdam by Saul Levi Morteira, Spinoza’s Rabbi - Mortera, Saul Levi (Amsterdam studies in the Dutch Golden Age, 2017)
Based on manuscript EH/LM48D38 (Fuks 206) of the Ets Haim Library, Amsterdam.